Testosterone deficiency worsens mitochondrial dysfunction in APP/PS1 mice - Zhang, Tianyun; Chu, Yun; Wang, Yue; Wang, Yu; Wang, Jinyang; Ji, Xiaoming; Zhang, Guoliang; Shi, Geming; Cui, Rui; Kang, Yunxiao (Frontiers in Aging Neuroscience, 2024)
Background Recent studies show testosterone (T) deficiency worsens cognitive impairment in Alzheimer’s disease (AD) patients. Mitochondrial dysfunction, as an early event of AD, is becoming critical hallmark of AD pathogenesis. However, currently, whether T deficiency exacerbates mitochondrial dysfunction of men with AD remains unclear. Objective The purpose of this study is to explore the effects of T deficiency on mitochondrial dysfunction of male AD mouse models and its potential mechanisms. Methods Alzheimer’s disease animal model with T deficiency was performed by castration to 3-month-old male APP/PS1 mice. Hippocampal mitochondrial function of mice was analyzed by spectrophotometry and flow cytometry. The gene expression levels related to mitochondrial biogenesis and mitochondrial dynamics were determined through quantitative real-time PCR (qPCR) and western blot analysis. SH-SY5Y cells treated with flutamide, T and/or H2O2 were processed for analyzing the potential mechanisms of T on mitochondrial dysfunction. Results Testosterone deficiency significantly aggravated the cognitive deficits and hippocampal pathologic damage of male APP/PS1 mice. These effects were consistent with exacerbated mitochondrial dysfunction by gonadectomy to male APP/PS1 mice, reflected by further increase in oxidative damage and decrease in mitochondrial membrane potential, complex IV activity and ATP levels. More importantly, T deficiency induced the exacerbation of compromised mitochondrial homeostasis in male APP/PS1 mice by exerting detrimental effects on mitochondrial biogenesis and mitochondrial dynamics at mRNA and protein level, leading to more defective mitochondria accumulated in the hippocampus. In vitro studies using SH-SY5Y cells validated T’s protective effects on the H2O2-induced mitochondrial dysfunction, mitochondrial biogenesis impairment, and mitochondrial dynamics imbalance. Administering androgen receptor (AR) antagonist flutamide weakened the beneficial effects of T pretreatment on H2O2-treated SH-SY5Y cells, demonstrating a critical role of classical AR pathway in maintaining mitochondrial function. Conclusion Testosterone deficiency exacerbates hippocampal mitochondrial dysfunction of male APP/PS1 mice by accumulating more defective mitochondria. Thus, appropriate T levels in the early stage of AD might be beneficial in delaying AD pathology by improving mitochondrial biogenesis and mitochondrial dynamics.